The influence of socioeconomic and cultural factors on emotional violence in gender-based abuse - Preeti Patel; Aiswarya Francis Xavier; Sentirenla Longchar; Subeksha Shrestha (Global Public Health)
Gender-based violence (GBV) remains a pervasive global issue that transcends cultural, geographic, and socio-economic boundaries. This study aims to contribute to the growing body of empirical literature on GBV by analysing its prevalence and associated factors across 19 countries using data from the Demographic and Health Surveys (DHS) Phases 7 and 8. While previous studies have often focused on physical or sexual violence, this research provides a holistic perspective, disaggregating findings across physical, sexual, and emotional violence. Further, special emphasis is placed on emotional violence, a subtle yet deeply harmful form of abuse that involves manipulation, humiliation, and control, with far-reaching psychological consequences. Our findings underscore the role of intergenerational violence, socio-economic disparities, and cultural norms in perpetuating emotional violence. Key determinants include childhood exposure to violence, educational attainment, economic dependence, and occupational vulnerabilities, with disparities observed across rural and urban settings. Emotional violence prevalence is particularly high among household workers and women in financially imbalanced relationships, highlighting the need for targeted interventions. The study identifies critical data gaps in understanding emotional violence and advocates for more in-depth questioning and qualitative research to capture its nuanced impacts.